İlahi Sevgi ve İnsan Izdırabı - Yıldız, İbrahim (Muş Alparslan Üniversitesi, 2020)
Aprominent claim endorsed by many theists and atheists in the literature on theproblem of evil is that God may permit human suffering only if the suffererbenefits from her suffering.  This claim, I argue, if taken seriously, would corrupt commonsense morality. Even thoughone may desire the best for another, no theist who takes the claim seriouslyhas good reason to alleviate suffering. Indeed, a theist who takes it seriously has reason to inflict suffering.  It is hard to imagine a greater corruption ofcommonsense morality than that

Tanrı’nın insan ızdırabına ancak eğer ızdıraba maruz kalanın çektiği ızdıraptan bir fayda elde edecekse izin vereceği iddiası kötülük problemi üzerindeki literatürde birçok teist ve ateist tarafından kabul edilen belirgin bir iddiadır. Bu iddianın, ciddiye alındığında, ortak (commonsense) ahlakı bozacağını iddia ediyorum. Biri başkası için en iyisini istese de, bu düşünceyi ciddiye alan bir teist, acıyı hafifletmek için herhangi bir nedenden yoksun kalır. Aslında bu düşünceyi ciddiye alan bir teistin haksız acı çektirmeye teşebbüs etmesi için sebebi vardır. Ortak ahlaka dair bundan daha büyük bir bozulma hayal etmek zordur
dinbil
Keywords: İlahi Sevgi; Acı; Izdırap